2014
DOI: 10.1001/jamasurg.2014.1227
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Related Attrition in General Surgery

Abstract: The current study demonstrated there was no association between female sex and attrition at our institution. Child rearing did not appear to be a risk factor for attrition in either men or women. Furthermore, child rearing did not negatively impact the quality of training based on case numbers and board pass rates. Despite prevalent stereotypes, child rearing did not cause women or men to leave the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…Pregnancy during obstetrics–gynecology residency did not impact the number of major procedures residents performed . In general surgery, women who had children born during training did not differ from their male counterparts in total case numbers or board pass rates …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Pregnancy during obstetrics–gynecology residency did not impact the number of major procedures residents performed . In general surgery, women who had children born during training did not differ from their male counterparts in total case numbers or board pass rates …”
Section: Discussionmentioning
confidence: 85%
“…11 In general surgery, women who had children born during training did not differ from their male counterparts in total case numbers or board pass rates. 12 A survey of plastic and reconstructive surgery PDs found that 36% of respondents discourage pregnancy due to the burden on coworkers, on the resident's training, or on the function of the department as a whole. 4 It is not surprising then that many PDs in our survey advised residents to plan pregnancy during research or elective rotations to lessen the strain on the program.…”
Section: Discussionmentioning
confidence: 99%
“…One common concern is that pregnant residents may fail to gain clinical experience due to maternity leave and other parenting duties or may drop out of residency (26). However, a recent study of general surgery residents demonstrated no negative impact on attrition rates, case numbers, or board pass rates for women or men who had children born during residency (27).…”
Section: Concerns Of Pregnant Radiation Oncology Traineesmentioning
confidence: 95%
“…Work by prior authors has shown that female residents with children do not look forward to work and are more likely to feel overwhelmed (20, 21). However, recent work has demonstrated that attrition rates were not influenced by child rearing regardless of gender (13). Training programs should consider implementing additional support systems for trainees or spouses who are pregnant, or doing a better job of advertising existing infrastructure, so that trainees feel they are adequately supported during such a stressful time period.…”
Section: Discussionmentioning
confidence: 99%
“…There was a time when a resident was expected to live at the hospital, and put the rest of his or her life on hold for the sake of professional immersion (5). With changes in GME expectations over the last century, punctuated by duty hour reforms in 2003 (6) and generational differences, trainees now may be less willing to postpone controllable life events (7–13). …”
mentioning
confidence: 99%